Improving Blood Pressure Control in Over-the-Road Truck Drivers: Is Provision of Medication Therapy Management by Pharmacists Feasible? - Keri D. Hager; Benjamin D. Aronson; Reid C. Smith; David Parra; Michael Swanoski (University of Minnesota Libraries Publishing, 2015)
Purpose This pilot sought to determine feasibility of studying the impact on hypertension in over-the-road truck drivers who met with pharmacists for Medication Therapy Management (MTM) compared to those who did not. Design/methodology/approach Drivers were randomly assigned to control or treatment (MTM) group for 52 weeks. Drivers assigned to the MTM arm could receive services in person or via secure videoconferencing technology located in a private space at the trucking company. All subjects were provided education and received a blood pressure monitor and log for recording daily blood pressures. Findings Eleven drivers enrolled and seven drivers completed the study. The primary barriers to participation included unpredictable driver schedules and lack of access to MTM provider while on the road. Research limitations/implications This pilot study was limited by small sample size. Pharmacists were not available to meet with truckers "on demand." Therefore, researchers are encouraged to test alternate opportunities to increase enrollment of drivers in studies and access to MTM services while drivers are on the road. Practical implications Hypertension is the second highest health-related cost burden, and over-the-road truck drivers have unique challenges that can make it difficult to attain blood pressure control. Pharmacist-provided MTM has been shown to improve blood pressure control. Improving access to MTM, perhaps using a national network of pharmacists or technology from the road, may decrease morbidity and mortality in drivers. Originality/value This paper fulfills an identified need to study how to improve driver access to care to reduce cardiovascular-related morbidity and mortality.   Type: Clinical Experience